Review and Potential Development of Solar Window Technology and Feasibility Study in Urban Area, Hong Kong as Case Study. Issue 2 (November 2020) - Chan, Ka Yan; Lee, Hei Yan; Lam, Tony Ngan Tung
Abstract: Net Zero Energy Building (NZEB) has been a rising topic in recent years, the route to achieve NZEB through renewable energy generation with the adaptation of solar window is explored. Literature review with current market research on the technology are studied and consolidated. Transformation from the current semi-transparent to future visibly transparent solar window is observed. Potential development of modular design with Wireless Power transfer is suggested for wide application of solar window. In the light of the large potential of solar window, feasibility study is conducted to analysis the application of the technology in Hong Kong context in term of the climate and installation criteria due to the Feed-In-Tariff (FiT). Solar analysis of solar resource availability and electricity generation are evaluated and simulated by Radiance using the morphologies of Central, Hong Kong as case study. Equations are developed for setting up selection criteria and estimating the suitable area for installation. 40.1% of solar insolation on an unobstructed horizontal plane was identified as threshold for installation in Hong Kong and the minimum installation is estimated to be 50 m 2 in order to be cost effective